Clinical use of ring with support pessary for advanced pelvic organ prolapse and predictors of its short-term successful use. Issue 8 (August 2017) - Deng, Mou; Ding, Jing; Ai, Fangfang; Zhu, Lan
Abstract: Objective: This study aimed to evaluate the success rate, patient satisfaction and adverse events with the use of the ring with support pessary in patients with advanced pelvic organ prolapse (POP), and to identify the factors associated with successful pessary use. Methods: In this prospective study, 151 patients with symptomatic advanced POP (POP quantification stage III/IV) came to the Centre of Obstetrics and Gynaecology, Peking Union Medical College Hospital, for POP treatment between May 2015 and December 2015. In all, 97 patients who chose the ring with support pessaries were included in this study. Successful pessary use was defined as the continuous use of the pessary at a 3-month follow-up visit. Independent-samples t tests, nonparametric tests, chi-square tests, Fisher's exact test, and logistic regression were used for data analysis. Results: In all, 82 patients continued to use the ring with support pessary for 3 months, whereas 15 patients discontinued, corresponding to a success rate of 84.5% (82/97). Most patients (80/82, 97.6%) who achieved success using the ring with support pessary felt satisfied. No severe complications were observed. Size 3 was the most commonly used size in our center (59.8% of the study patients). Predominant anterior wall prolapse was associated with the successful use of ring with support pessary (odds ratio 5.08, 95% confidence interval 1.33-19.43, P  = 0.02). Conclusions: The ring with support pessary was successfully used for the treatment of advanced POP with high rates of success and satisfaction. A predominant prolapse in the anterior wall may be a potential influence factor for successful pessary use.